2006
DOI: 10.1093/pcp/pcj081
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Knock-Down of ENOD40 s Leads to Significant Suppression of Nodule Formation in Lotus japonicus

Abstract: ENOD40 is one of the most intriguing early nodulin genes that is known to be induced very early in response to interaction of legume plants with symbiotic Rhizobium bacteria, but its function in the nodulation process is still not known. Lotus japonicus has two ENOD40 genes: LjENOD40-1 is abundantly induced in very early stages of bacterial infection or Nod factor application, whereas LjENOD40-2 is abundantly expressed only in mature nodules. We generated transgenic lines of L. japonicus with an RNAi (RNA inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 32 publications
3
39
0
1
Order By: Relevance
“…32 RNAi experiments in Lotus japonicus demonstrated that ENOD40 knockdown inhibited nodule primordium development, but not rhizobial infection. 33 A similar reduction in nodule formation was found for alfalfa transgenic plants with reduced ENOD40 levels brought about by cosuppression. 28 Earlier, we showed that when an alfalfa Nod -mutant (mutated in MsNORK/MtDMi2) was treated with the cytokinin 6-benzylaminopurine, ENOD40 gene expression was up-regulated, demonstrating that application of this phytohormone could bypass the Nod factor-triggered signal transduction pathway.…”
Section: Cytokinin Triggers Enod40 Expression In Melilotussupporting
confidence: 60%
“…32 RNAi experiments in Lotus japonicus demonstrated that ENOD40 knockdown inhibited nodule primordium development, but not rhizobial infection. 33 A similar reduction in nodule formation was found for alfalfa transgenic plants with reduced ENOD40 levels brought about by cosuppression. 28 Earlier, we showed that when an alfalfa Nod -mutant (mutated in MsNORK/MtDMi2) was treated with the cytokinin 6-benzylaminopurine, ENOD40 gene expression was up-regulated, demonstrating that application of this phytohormone could bypass the Nod factor-triggered signal transduction pathway.…”
Section: Cytokinin Triggers Enod40 Expression In Melilotussupporting
confidence: 60%
“…To investigate if nodulin gene expression was affected by SIE3 RNAi, we examined the expression levels of NIN and ENOD40-2, two early nodulin genes implicated in the processes of rhizobial entrance, nodule initiation, and subsequent organogenesis (Schauser et al, 1999;Kumagai et al, 2006), as well as the expression of Lb (for leghemoglobin), a typical nodulin gene required for nitrogen fixation (Ott et al, 2005). Real-time PCR analysis showed that the expression levels of the two early nodulin genes (NIN and ENOD40-2), but not Lb, were reduced drastically in the SIE3 RNAi hairy roots, as compared with those in the control hairy roots ( Fig.…”
Section: Suppression Of Rhizobial Infection By Sie3 Rnaimentioning
confidence: 99%
“…We scored IT numbers in SIE3 RNAi hairy roots 8 d after rhizobial inoculation. ITs were visible as blue threads under a microscope after staining with 5-bromo-4-chloro-3-indolyl-b-Dgalactopyranoside acid (X-gal) that reacted with the lacZ-labeled M. loti cells (Tansengco et al, 2003;Kumagai et al, 2006). ITs were divided into four groups according to the cellular locations of their growing tips: 1) those emerging from curled root hairs, 2) those growing from elongated root hairs to the root epidermis, 3) those penetrating through the root cortex, and 4) those reaching to the nodule primordia, as shown in Supplemental Figure S7.…”
Section: Suppression Of Rhizobial Infection By Sie3 Rnaimentioning
confidence: 99%
“…Primers for the Enod40-1, Enod40-2, and Nin primers were described previously (Kumagai et al 2006). The Ljmate1 primers were described by Takanashi et al (2013).…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%